2020
DOI: 10.1038/s42003-020-0882-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular bases for HOIPINs-mediated inhibition of LUBAC and innate immune responses

Abstract: The NF-κB and interferon antiviral signaling pathways play pivotal roles in inflammatory and innate immune responses. The LUBAC ubiquitin ligase complex, composed of the HOIP, HOIL-1L, and SHARPIN subunits, activates the canonical NF-κB pathway through Met1-linked linear ubiquitination. We identified small-molecule chemical inhibitors of LUBAC, HOIPIN-1 and HOIPIN-8. Here we show that HOIPINs down-regulate not only the proinflammatory cytokine-induced canonical NF-κB pathway, but also various pathogen-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 68 publications
4
73
0
Order By: Relevance
“…There is considerable interest in the development of small molecule modulators of RBR E3 activity as chemical tools for dissecting RBR signalling pathways, and for therapeutic applications. Covalent inhibitors that irreversibly modify the active site cysteine and inhibit activity have been developed for HOIP, and in principle this approach could be extended to other RBR E3s [67][68][69][70]. Structure-guided inhibitor design permits rational optimisation of hit compounds, although crystallisation of RBRs is often hampered by inherent interdomain flexibility.…”
Section: Box 1: Targeting Rbr E3s With Small Moleculesmentioning
confidence: 99%
“…There is considerable interest in the development of small molecule modulators of RBR E3 activity as chemical tools for dissecting RBR signalling pathways, and for therapeutic applications. Covalent inhibitors that irreversibly modify the active site cysteine and inhibit activity have been developed for HOIP, and in principle this approach could be extended to other RBR E3s [67][68][69][70]. Structure-guided inhibitor design permits rational optimisation of hit compounds, although crystallisation of RBRs is often hampered by inherent interdomain flexibility.…”
Section: Box 1: Targeting Rbr E3s With Small Moleculesmentioning
confidence: 99%
“…However, some studies suggested that the LUBAC activity is necessary for the TLR-mediated IRF3 activation [69][70][71], and LUBAC is reportedly indispensable for the TNF-induced TBK1 and IKKε activation and prevention of cell death [72]. We showed that the LPS-, poly(I:C)-, and SeV-mediated IFN production pathway was impaired in HOIP-deficient mouse embryonic fibroblasts and human Jurkat T-lymphoblasts, and LUBAC inhibitors, HOIPINs, suppressed the antiviral pathway through the reduced activation of TBK1 and IRF3, supporting the positive function of LUBAC in this pathway [73]. Further studies are required to clarify the function of LUBAC in the IFN antiviral pathway.…”
Section: Lubac-mediated Regulation Of Interferon Signalingmentioning
confidence: 65%
“…From these studies, we hypothesized that the aggregable proteins in wisp inclusions may be initially conjugated with K48-linked ubiquitin chains; however, they seem to be resistant to the proteasomal degradation due to misfolding (Figure 6). Concomitant with aging, maturation, and liquid-liquid phase separation (LLPS), LUBAC-mediated linear ubiquitin and/or K63-linked We recently determined that HOIPINs are conjugated to the active site Cys885 in the RING2 domain of HOIP through Michael addition, and interrupt the RING-HECT-hybrid reaction in HOIP [73]. The benzoate, 2,6-difluorophenyl, and 1H-pyrazol-4-yl moieties of HOIPIN-8 interact with Arg935 and Asp936, which are located in the LDD domain of human HOIP ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations